The Factors Correlating to Low Back Pain in Nurses at Annisa Hospital Pekanbaru - Parlin, W (KnE Life Sciences, 2019)
The disease that generally occurs on the labors is low back pain. Low back pain is a condition of acute pain or chronic and inconvenience aroud lumbosacral, caused by inflammation, degenerative, malignancy, and gynecology disorder, trauma, or metabolism disorder. The purpose of this research is to know the correlation between work posture, IMT, work period, work length, work shift, age and the occurance of low back pain on the nurses at Annisa Hospital. The type of this research is quantitative research with cross sectional approach. The population in this research were all nurses at Annisa Hospital Pekanbaru in total 126 nurses by using Total Sampling technique. The research instruments used were questionnaire, scales, height gauge, RULA, and observation sheet. The data were obtained through questionnaires. The analysis was by using chi-square test with α = 0.05 and logistic binary test. The research results show that the variables having significant correlation are work posture, IMT, and age. The results of this research can used to decrease the occurance of low back pain in nurses at the hospital. The conclusion of this research is the factors which have correlation to the complain on low back pain in the nurses at Annisa Hospital are work posutre, IMT, and age. It is expected that nurses perform work attitude correctly and do exercise 3 to 5 times in a week for ≥ 30 minutes, and achieve ideal body weight. Keywords: Low back pain occurance, work posture, IMT, and Age.